Pharmacokinetics of Chloroquine and Monodesethylchloroquine in Pregnancy - Karunajeewa, H.; Salman, S.; Mueller, I.; Baiwog, F.; Gomorrai, P.; Law, I.; Page-Sharp, Madhu; Rogerson, S.; Siba, P.; Ilett, K.; Davis, T. (American Society for Microbiology, 2010)
In order to determine the pharmacokinetic disposition of chloroquine (CQ) and its active metabolite, desethylchloroquine (DECQ), when administered as intermittent presumptive treatment in pregnancy (IPTp) for malaria, 30 Papua New Guinean women in the second or third trimester of pregnancy and 30 age-matched nonpregnant women were administered three daily doses of 450 mg CQ (8.5 mg/kg of body weight/day) in addition to a single dose of sulfadoxine-pyrimethamine. For all women, blood was taken at baseline; at 1, 2, 4, 6, 12, 18, 24, 30, 48, and 72 h posttreatment; and at 7, 10, 14, 28, and 42 days posttreatment. Plasma was subsequently assayed for CQ and DECQ by high-performance liquid chromatography, and population pharmacokinetic modeling was performed. Pregnant subjects had significantly lower area under the plasma concentration-time curve for both CQ (35,750 versus 47,892 µg·h/liter, P < 0.001) and DECQ (23,073 versus 41,584 µg·h/liter, P < 0.001), reflecting significant differences in elimination half-lives and in volumes of distribution and clearances relative to bioavailability. Reduced plasma concentrations of both CQ and DECQ could compromise both curative efficacy and posttreatment prophylactic properties in pregnant patients. Higher IPTp CQ doses may be desirable but could increase the risk of adverse hemodynamic effects.